2012
DOI: 10.1093/cercor/bhs115
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Mitigates Brain Injury in a Rat Model of Infection-Sensitized Neonatal Hypoxia-Ischemia

Abstract: Intrauterine infection exacerbates neonatal hypoxic-ischemic (HI) brain injury and impairs the development of cerebral cortex. Here we used low-dose lipopolysaccharide (LPS) pre-exposure followed by unilateral cerebral HI insult in 7-day-old rats to study the pathogenic mechanisms. We found that LPS pre-exposure blocked the HI-induced proteolytic activity of tissue-type plasminogen activator (tPA), but significantly enhanced NF-κB signaling, microglia activation, and the production of pro-inflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…Activation of microglia and innate immunity is considered a major component contributing to immature brain injury (55,56). sPIF treatment resulted in reduced microglial activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of microglia and innate immunity is considered a major component contributing to immature brain injury (55,56). sPIF treatment resulted in reduced microglial activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…121,122 Other studies have shown that inhibition of inflammation by intracerebroventricular injection of a stable, mutant form of plasminogen activator protein-1, given up to 4 hours after the onset of LPS-sensitized hypoxia-ischaemia, reduced hypoxia-ischaemia-induced blood-brain barrier damage, microglial activation, and brain tissue loss. 123 Furthermore, we recently demonstrated that blocking sensitizing inflammation with a novel class of innate defence regulator peptide (IDR-1018) provided marked neuroprotection and modulated inflammation. This effect was observed even when the peptide was given 3 hours after the induction of LPS-sensitized hypoxia-ischaemia.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Transient hypoxic ischemia (tHI), which was applied 45 min after HI, followed by reperfusion in neonatal rat brains was performed as previously described, with minor modifications (37,38). Since we found that GAP43-gephyrin interaction was induced during the reoxygenation/reperfusion period in the in vitro tHI (see Fig.…”
Section: S41amentioning
confidence: 99%